2001
DOI: 10.1029/2000gl012577
|View full text |Cite
|
Sign up to set email alerts
|

Emission cross section of O I (135.6 nm) at 100 eV resulting from electron‐impact dissociative excitation of O2

Abstract: In this Letter, we report for the first time, the ratio o• tn• O • (1•.• •)/O I (1•0.4 •) •o•ut• •i•io• cross sections from electron-impact dissociative excitation of 02 at 100 eV using facilities located at the University of Colorado, Laboratory for Atmospheric and Space Physics (LASP). The O I (135.6 nm) emission glow produced in the laboratory from the long-lived transition O I gap •_ 5SO was measured in a large collision chamber (lm diameter) with a long focal length (50 cm) electrostatic electron gun. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Wells et al [1971] found the cross section for dissociative excitation to be 1.1 Â 10 À17 cm 2 at 100 eV. We can now correct the Ajello [1971] calculation at 100 eV for the current shorter lifetime of 180 ms. We find that the corrected result agrees closely with our more accurate measurement of the OI(135.6 nm) emission cross section at 100 eV, described in section 3 and by Noren et al [2001].…”
Section: Introductionsupporting
confidence: 88%
“…Wells et al [1971] found the cross section for dissociative excitation to be 1.1 Â 10 À17 cm 2 at 100 eV. We can now correct the Ajello [1971] calculation at 100 eV for the current shorter lifetime of 180 ms. We find that the corrected result agrees closely with our more accurate measurement of the OI(135.6 nm) emission cross section at 100 eV, described in section 3 and by Noren et al [2001].…”
Section: Introductionsupporting
confidence: 88%
“…We have successfully constructed a large vacuum system apparatus for measuring the emission cross sections of two of the strongest optically forbidden transitions found in the Mars airglow: O i (135.6 nm; reported in this paper) and the Cameron bands in the MUV (in preparation). The experimental apparatus for emission cross sections has been discussed in detail previously (Ajello et al, ; Kanik et al, ; Noren et al, ). We have published the initial work 10 years ago on O i ( 135.6 nm) from dissociation of O 2 using the Cassini UVIS flight‐spare (Kanik et al, ; Makarov et al, ).…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The experimental apparatus for emission cross sections has been discussed in detail previously [ Noren et al , ; Kanik et al , ]. We have previously published the work on O i (135.6 nm) from dissociation of O 2 using the Cassini UVIS (Ultraviolet Imaging Spectrograph) [ Kanik et al , ; Makarov et al , ].…”
Section: Experimental Apparatusmentioning
confidence: 99%